MARKET ORIENTATION, ORGANIZATIONAL LEARNING, INNOVATION AND PERFORMANCE: KEYS TO THE SUSTAINABILITY OF NON-PROFITS - Fonseca, Susana; Baptista, Alberto (European Scientific Journal, ESJ, 2013)
The purpose of this paper is to review literature, exploring the relationships between the concepts market orientation, organizational learning, innovation and performance in nonprofit organizations. To understand the nature of these concepts in the nonprofit context, the authors will discuss their application to nonprofit organizations. It questioned the use of management methodologies in these organizations and suggests the investigation of its application to improve its performance. The management of nonprofit organizations should move to another setting, unlike the informality that characterizes them. The question which arises is this reality that these organizations as complex organizations, should strive to implement new management tools that enable them to achieve sustainability, while they seek to achieve their social mission in the universe that are inserted. Thus, the authors propose a conceptual model that relates the concepts above and presents the hypotheses to be tested. They conclude by suggesting the application of the empirical model NPO management as a line of future research. The paper presented, which is part of a broader work of a doctoral thesis, refers mainly to literature.